Transition-metal-free, one-pot synthesis of benzoxaboroles from o-bromobenzaldehydes via visible-light-promoted borylation. Issue 47 (24th November 2021) - Luo, Jinghan; Jia, Xingxing; Hu, Yanjun; Chen, Jianchao; Sun, Tiemin
Abstract : A novel and practical approach for the synthesis of benzoxaboroles from o -bromobenzaldehydes is described via visible-light-promoted borylation. Abstract : A novel and simple one-pot stepwise method to synthesize benzoxaboroles was demonstrated. This step-by-step synthetic method includes photocatalytic boronization with phenothiazine as a photocatalyst and sequential water-induced reduction in the presence of bis(pinacolato)diboron. A series of o -bromobenzaldehydes were well-tolerated under the standard conditions. In addition, this method has been successfully applied in the synthesis of the anti-tuberculosis candidate drug GSK 3036656 and anti-fungal drug tavaborole.